Encouraging physical development through movement-play - Archer, Carol; Siraj, Iram (SAGE, 2016)
'Movement-play' encourages physical activity in a child-led manner for the benefit of children's health, learning and wellbeing. This book looks at the theory behind the importance of movement and how movement-play works within Early Years settings. It also provides practical advice on its implementation.- Resumé vydavatel
Keywords: tělovýchova; motorické schopnosti; děti; předškolní výchova; hra; physical education; motor abilities; children; preschool education; play; elektronické knihy; monografie; electronic books; monographs